Emergency laparoscopic cholecystectomy for hemorrhagic cholecystitis: A case report. (December 2021) - Nitta, Toshikatsu; Iida, Ryo; Ishii, Masatsugu; Ueda, Masahiko; Senpuku, Sadakatsu; Matsutani, Ayumi; Ishibashi, Takashi
Abstract: Introduction: Hemorrhagic cholecystitis (HC) is a rare but specific complication of acute cholecystitis. HC progression often leads to fatal and severe outcomes. Presentation of case: We describe the case of a 64-year-old man who was diagnosed with HC. Intraoperatively, the gallbladder surface was congested. The resected specimen had no gallstones and showed basophilic degenerate material toward the mucosal surface. In addition, vascular congestion and red cell extravasation were noted at the bottom of the layer. The patient's postoperative course was good, and he was discharged with remission 4 days following the operation. Discussion: Diagnosis and treatment during early stages are the most critical aspects of HC management and may lead to improved outcomes. We successfully performed timely laparoscopic cholecystectomy for the treatment of HC. Conclusion: In cases where HC occurs, appropriate treatment should be chosen by experiential judgment and consideration of the current literature. Highlights: We observed that the surface of the gallbladder was congested and we diagnosed the hemorrhagic cholecystitis We successfully performed timely laparoscopic cholecystectomy for the treatment of hemorrhagic cholecystitis as an emergency operation.